2019
DOI: 10.1177/1076029619852167
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Deep Vein Thrombosis Following Elective Knee Arthroscopy Over the Age of 40

Abstract: Thromboprophylaxis following arthroscopic knee surgery (AKS) is not clear in the literature. The purpose of this study was to present the incidence of symptomatic deep vein thrombosis (DVT) following elective AKS over the age of 40. The secondary purpose was to investigate risk factors associated with venous thromboembolic events (VTEs). Surgical database and outpatient clinic follow-up charts of the patients who underwent AKS for any reason were included in the study. Odds for risk factors such as previous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…No statistical difference was observed between groups, in terms of smoking and alcohol intake, in the present study, despite the historical evidence supporting the positive correlation between smoking and postoperative DVT risks. 22,26 In the present study, predominant patients with a positive tobacco or alcohol use history were male (smoking [M:F] 336:9; drinking [M:F] 231:16). The univariate analysis on male tobacco and male alcohol users revealed that a higher proportion of symptomatic DVT patients reported a smoking history, when compared with male controls (P ¼ 0.008), favoring the conclusion that smoking can be a risk factor in postoperative DVT.…”
Section: Discussionmentioning
confidence: 67%
“…No statistical difference was observed between groups, in terms of smoking and alcohol intake, in the present study, despite the historical evidence supporting the positive correlation between smoking and postoperative DVT risks. 22,26 In the present study, predominant patients with a positive tobacco or alcohol use history were male (smoking [M:F] 336:9; drinking [M:F] 231:16). The univariate analysis on male tobacco and male alcohol users revealed that a higher proportion of symptomatic DVT patients reported a smoking history, when compared with male controls (P ¼ 0.008), favoring the conclusion that smoking can be a risk factor in postoperative DVT.…”
Section: Discussionmentioning
confidence: 67%
“…Knowledge of Virchow's triad (hypercoagulability, endothelial injury and venous stasis) and the mechanisms of production of thromboembolic disease, can help guide thromboprophylaxis in individual situations where there is no specific evidence 351 . Hardware removal could be stratified as complicated or not with respect to the difficulty of removal, surgical time, bony manipulation, use of tourniquet, and need for general anesthesia.…”
Section: -Is Routine Vte Prophylaxis Indicated In Patients With Immob...mentioning
confidence: 99%
“…The authors found that a tourniquet time of > 2 hours increased the incidence of DVT from 12.1% to 17.4%, and the extended time was associated with a combined ACL reconstruction and concomitant procedures. 13 In a recent study by Özcan et al, 14 the authors studied the incidence of DVT in patients above the age of 40 compared with patients under 40 years of age in patients undergoing knee arthroscopy. A total of 1385 patients were included in the study (610 patients > 40 y of age), and the overall instance of VTE was 0.79% (n = 11).…”
Section: Kneementioning
confidence: 99%
“…The authors recommended that thromboprophylaxis be considered for these at-risk patients, noting the importance of understanding the risk factors as they specifically relate to the patient, their medical history, and their current medical conditions when determining thromboprophylaxis use. 14 In the adolescent population, future research is necessary to determine the risks and necessity of thromboprophylaxis. Murphy et al 16 found that all adolescent patients that developed a VTE postoperatively had at least 1 risk factor; however, given the lack of high-level evidence, the authors recommended that early mobilization, when possible, is a feasible prevention technique and to only consider the lowest risk forms of thromboprophylaxis (eg, short-term aspirin) for older adolescents (above 15 y).…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation